DISTRIBUSI SPASIAL FLUKS KARBON DIOKSIDA DI PERAIRAN KARIMUNJAWA, INDONESIA - Nurul Latifah; Hadi Endrawati; Sigit Febrianto (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
Global warming phenomena occures as result of the increase of the amount of greenhouse gases in the atmosphere which is dominated by anthropogenic CO2 (carbon dioxide). These conditions cause climate change on the earth. Therefore, the absorption of carbon dioxide gas in the atmosphere is needed, one of which is through an ocean processes called blue carbon. The purpose of this study was to determine the potential of blue carbon absorption (fluxes CO2) in Karimunjawa waters. This research was conducted in the waters around Karimunjawa Island in May 2018. The research method used a survey method with a quantitative approach. Samples were taken at 15 observation stations of Karimunjawa Island using purposive sampling method. Analysis of carbonate system data by titrimetric method. The results showed that most of Karimunjawa waters (13 stations) functioned as source of CO2 with a range of CO2 flux values between 1.79 to 21.64 mmolCO2/m2/day where the flow of CO2 moved from the ocean to the atmosphere. While the other 2 stations function as sink of CO2 where the flow of CO2 moved from the atmosphere to the ocean with a range of CO2 fluxes of -3.69 to -4.41 mmolCO2/m2/day. The pattern of CO2 fluxes followed a pattern of ∆pCO2, DIC, total alkalinity, salinity, pH. The CO2 flux pattern follows the pattern of changes in ∆pCO2, DIC, total alkalinity, salinity and pH. The spatial distribution of potential blue carbon uptake (fluxes CO2) in Karimunajwa waters as a release of CO2 from the oceans into the atmosphere with a positive flux CO2 value.